Proposal of a specific classification of primary periphyseal stress injuries in adolescent rock climbers - Schöffl, V.; Iruretagoiena, X.; Nelson, T.; Miro, Paulo (Frontiers in Sports and Active Living, 2025)
IntroductionPrimary Periphyseal Stress Injuries (PPSI) of the hand and fingers are relatively uncommon but are most frequently seen in adolescent rock climbers. A major limitation in the current literature on PPSIs is the lack of a standardized nomenclature and radiological classification. This gap complicates the accurate diagnosis, treatment, and comparison of outcomes across studies.MethodsWe conducted a comprehensive structured literature review of the relevant PPSI literature in climbers using Pubmed, SPORTDiscus, and Web of Science to identify the relevant studies on PPSI in adolescent rock climbers. Based on the findings from existing research and our own data, we propose a new classification system for these injuries.ResultsA five-grade classification system, with subgroups, has been developed based on both clinical and radiographic data. The classification is presented in a table, along with figures illustrating examples of the various injury types.ConclusionAdditional research is required to assess the reliability and reproducibility of this classification system. We plan to conduct these evaluations in future studies.